EAACI position paper: Comparing insect hypersensitivity induced by bite, sting, inhalation or ingestion in human beings and animals - Pali-Schöll, Isabella; Blank, Simon; Verhoeckx, Kitty; Mueller, Ralf S; Janda, Jozef; Marti, Eliane; Seida, Ahmed A; Rhyner, Claudio; DeBoer, Douglas J; Jensen-Jarolim, Erika (Allergy, 2019)
Adverse reactions to insects occur in both human and veterinary patients. Systematic comparison may lead to improved recommendations for prevention and treatment in all species. In this position paper, we summarize the current knowledge on insect allergy induced via stings, bites, inhalation or ingestion, and compare reactions in companion animals to those in people. With few exceptions, the situation in human insect allergy is better documented than in animals. We focus on a review of recent literature and give overviews of the epidemiology and clinical signs. We discuss allergen sources and allergenic molecules to the extent described, and aspects of diagnosis, prophylaxis, management and therapy.
Keywords: Animals; Phenotype; Allergens; alergie; lidé; kousnutí a bodnutí hmyzem; kůže; Insect Bites and Stings; Hypersensitivity; určení symptomu; hmyz; ochrana veřejného zdraví; Skin; Disease Susceptibility; Public Health Surveillance; Disease Management; alergeny; Symptom Assessment; fenotyp; zvířata; Insecta; management nemoci; náchylnost k nemoci; Humans